GE_GERICHTE P/15147/2020 vom 29. August 2024 - GE Cour de justice (2024)
IN DUBIO PRO REO;BRIGANDAGE;CHANTAGE;CONTRAINTE(DROIT PÉNAL);TENTATIVE(DROIT PÉNAL);FIXATION DE LA PEINE;CONCOURS D'INFRACTIONS | CP.140.al1; CP.156; CP.181; CP.183.al1; CP.22.al1; CP.47; CP.49.al1